1998
DOI: 10.1183/09031936.98.11020422
|View full text |Cite
|
Sign up to set email alerts
|

Effects of proportional assist ventilation on exercise tolerance in COPD patients with chronic hypercapnia

Abstract: This study investigates the impact of proportional assist ventilation (PAV), a new mode of partial ventilatory support, on exercise tolerance and breathlessness in severe hypercapnic chronic obstructive pulmonary disease (COPD) patients. We also examined the effects of continuous positive airway pressure (CPAP) and pressure support ventilation (PSV). On two consecutive days, 15 stable hypercapnic COPD patients underwent four endurance tests on a cycle ergometer at 80% of their maximal workrate, receiving, via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
3
18

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(119 citation statements)
references
References 34 publications
4
94
3
18
Order By: Relevance
“…The data of this study confirm and extend previous observations, in patients with chronic respiratory insufficiency from both restrictive and obstructive diseases. It was shown that nasal-mask application of PAV improved the breathing pattern and arterial blood gases [1] and provided ventilatory assistance during exercise in severe nonhypercapnic [17] and hypercapnic [2] stable COPD patients. Other investigators have shown that PAV can unload the inspiratory muscles also in ventilatordependent intubated patients with acute respiratory failure due to exacerbation of COPD [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The data of this study confirm and extend previous observations, in patients with chronic respiratory insufficiency from both restrictive and obstructive diseases. It was shown that nasal-mask application of PAV improved the breathing pattern and arterial blood gases [1] and provided ventilatory assistance during exercise in severe nonhypercapnic [17] and hypercapnic [2] stable COPD patients. Other investigators have shown that PAV can unload the inspiratory muscles also in ventilatordependent intubated patients with acute respiratory failure due to exacerbation of COPD [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…After those 40 min, FA and VA were combined to deliver PAV for an additional 40 min. Then, CPAP was increased 2±5 cmH 2 O for an additional 20 min. In two patients the signal from the gastric balloon became unsatisfactory during the course of the experimental procedure.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations